Validation of the Australian beverage picture set: A controlled picture set for cognitive bias measurement and modification paradigms. (14th October 2019) - Onie, Sandersan; Gong, Sharon; Manwaring, Elizabeth; Grageda, Dayanna; Webb, Kyra; Yuen, Wing See; Most, Steven B.
Abstract: Objective: Research on implicit biases toward alcoholic stimuli require validated picture sets that (a) contain a wide range of alcoholic and non‐alcoholic beverages recognised by the sample population, (b) control for featural differences that do not pertain to the beverage itself, and (c) elicit a desired effect upon viewing, with alcoholic beverages resulting in an increased urge to drink in heavy drinkers. To validate the Australian Beverage Picture Set (OzBPS); a stimulus set to be used in alcohol‐related cognitive bias research in Australian populations. Method: A range of alcoholic and non‐alcoholic beverages were photographed under controlled conditions in both active (opening, serving, drinking and pouring) and passive contexts (beverage, beverage with empty glass, beverage with full glass). Following that, 98 undergraduates completed an identification and ratings task (measuring valence, arousal, urge to drink and familiarity). Finally, participants completed a questionnaire indexing alcohol consumption. Results: After eliminating beverages that were not easily identified as alcoholic or non‐alcoholic, the analysis validated the picture set, revealing a linear relationship between habitual heavy drinking and an increased urge to drink in response to alcoholic beverages. Furthermore, we included a novel pouring context, which was found to elicit a stronger urge to drink compared to other drinking contexts. Conclusions: The OzBPS is a valid image set that will facilitate future research into cognitive correlates of drinking behaviour.